PERCEPTION OF STUDENTS ON TEACHING QUALITY: A STUDY OF ONE ISLAMIC UNIVERSITY - Muhamad Taufik Hidayat; Atika Azzahro Hazima; Achmad Januar Arifin; Putri Pramesti Hening; Annisa Fitri; Tivana Aulia Sasmito (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
The Student Evaluation of Teaching (SET) is a critical tool for ensuring the quality of higher education. However, SET results do not always comprehensively capture students' perspectives. Factors such as ambiguous evaluation forms, varying interpretations of questions, and the influence of non-academic factors on student responses can impact the reliability of the results. This research aims to reveal students' positive perceptions of the SET and uncover students' negative perceptions of the SET. This study employs a qualitative research method with a descriptive approach. The participants consisted of eight informants, including lecturers and students. Data collection methods included in-depth interviews. The data were analyzed using a thematic approach. The validity of the data was ensured through check and recheck, researcher diligence, time triangulation, researcher triangulation, rechecking, and confirmation with informants. The findings indicate that informants held positive and negative perceptions of various aspects of the learning process. Seven key criteria related to student satisfaction were identified, spanning both offline and online learning environments. These criteria were based on student evaluations conducted at the end of each semester. Overall, the perceptions provided by the informants were consistent with the lecturers' expertise and understanding in their respective fields.